Design of a solar low temperature steam generation system - Kalogirou, Soteris A. (My University, 1996)
The three methods employed for solar steam generation are analyzed with respect to their advantages, operating problems, operational stability, and cost. From this analysis the steam-flash system is selected because it has advantages with respect to other systems due to the superiority of the water as a heat transfer fluid, the relatively low capital cost, and the avoidance of any flow stability problems. The design of the flash vessel, which is the main part of the system, is then presented. The flash vessel size and inventory determines how much energy is invested in heating-up the system in the morning therefore optimisation of the system is necessary. Finally design graphs for the optimum flash vessel design are given. These graphs can be used for a quick design of the flash vessel inventory, diameter and height within the range considered here, up to a collector aperture area of about 2200 m2.
Keywords: Solar energy